2018
DOI: 10.1038/s41388-018-0295-z
|View full text |Cite
|
Sign up to set email alerts
|

MASTL overexpression promotes chromosome instability and metastasis in breast cancer

Abstract: MASTL kinase is essential for correct progression through mitosis, with loss of MASTL causing chromosome segregation errors, mitotic collapse and failure of cytokinesis. However, in cancer MASTL is most commonly amplified and overexpressed. This correlates with increased chromosome instability in breast cancer and poor patient survival in breast, ovarian and lung cancer. Global phosphoproteomic analysis of immortalised breast MCF10A cells engineered to overexpressed MASTL revealed disruption to desmosomes, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(103 citation statements)
references
References 44 publications
(65 reference statements)
11
89
1
Order By: Relevance
“…Chromosome segregation errors can promote the number of micronuclei that when ruptured, cause enhanced cytosolic DNA, activate downstream noncanonical NF-kB signaling, and activate the cytosolic DNA-sensing cGAS-STING pathway in CIN-high breast cancer cells, hence stimulating cancer metastases (69). The amplification and overexpression of MASTL, an essential kinase for correct progression through mitosis, correlates with enhanced CIN in breast cancer and poor patient survival, whereas knockdown of MASTL may suppress breast cancer metastasis in vivo (70). CIN has also been suggested to initiate the formation of somatic copy-number alterations (SCNA; ref.…”
Section: Breast Cancermentioning
confidence: 99%
“…Chromosome segregation errors can promote the number of micronuclei that when ruptured, cause enhanced cytosolic DNA, activate downstream noncanonical NF-kB signaling, and activate the cytosolic DNA-sensing cGAS-STING pathway in CIN-high breast cancer cells, hence stimulating cancer metastases (69). The amplification and overexpression of MASTL, an essential kinase for correct progression through mitosis, correlates with enhanced CIN in breast cancer and poor patient survival, whereas knockdown of MASTL may suppress breast cancer metastasis in vivo (70). CIN has also been suggested to initiate the formation of somatic copy-number alterations (SCNA; ref.…”
Section: Breast Cancermentioning
confidence: 99%
“…Furthermore, increased MASTL expression has been associated with poor outcomes in breast, oral, gastric, colon, and head and neck cancer, suggesting that MASTL plays a master role in carcinogenesis. [24][25][26]49,[52][53][54] Disrupting the MASTL-ENSA-PP2A-B55 (MEP) axis results in multiple mitotic errors 21,50,55,56 which then drive CIN, a hallmark of cancer. 57 Recent studies have also demonstrated that MASTL promotes oncogenesis and therapy resistance in cancer cells by enhancing oncogenic AKT kinase activity 54 and Wnt signaling.…”
Section: Cellular Transformation and Oncogenic Signaling Pathwaysmentioning
confidence: 99%
“…24,52,53,58 Similar studies in breast cancer have demonstrated that MASTL expression correlates significantly with increased CIN, mitotic index, histological grade, poor overall survival and with a high risk of metastatic relapse in estrogen receptor (ER) positive patients. 25,49,52,59 Overexpression of wild-type MASTL in immortalized human MCF10A breast epithelial cells was sufficient to increase the rate of chromosome bridges, micronuclei formation as well as to induce loss of contact inhibition, 25,54 whereas inhibition of MASTL selectively killed breast cancer cells by induction of mitotic catastrophe. 52 Other than its effects on mitosis, MASTL promotes oncogenesis by activating AKT kinase activity via degradation of its phosphatase, PH (pleckstrin homology) domain Leucine-rich repeat Protein Phosphatase (PHLPP), 54 regulates normal DNA replication timing 60 and recovery from the premitotic DNA damage checkpoint arrest.…”
Section: Cellular Transformation and Oncogenic Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations